Sex Differences in Determinants of Suicide Risk Preceding Psychiatric Admission: An Electronic Medical Record Study - McQuaid, Robyn J.; Nikolitch, Katerina; Vandeloo, Katie L.; Burhunduli, Patricia; Phillips, Jennifer L. (Frontiers in Psychiatry, 2022)
Background: Individuals requiring inpatient psychiatric care represent a group at higher risk of progressing toward suicide attempt. Using electronic medical record (EMR) data collected from psychiatric inpatient admissions, the objective of this study was to identify sex differences in risk factors for suicide plans and/or attempts within the 30 days preceding hospital admission. Methods: Resident Assessment Instrument for Mental Health (RAI-MH) intake data were obtained for patients admitted to a Canadian tertiary-care hospital deemed a ‘threat or danger to self’ during a ten-year period (2008-2018). Data was extracted for individuals categorized into three groups: non-suicidal (N=568), presence of suicide plan (N=178), and presence of suspected suicide attempt (N=124) in the 30 days prior to hospital admission. Multivariate logistic regression models were used to examine determinants of suicide risk. Results: Across all models, diagnosis of depression was the strongest predictor of suicide plan and/or attempt (OR=5.54, 95% CI=3.71-8.27, p<.001). Comparing clinical symptoms between suicidal and non-suicidal groups at the time of admission, the largest effect sizes were found for hopelessness (p<.001, η2= .11), and guilt or shame (p<.001, η2=.09). Female sex was identified as a significant factor for elevated suicidal risk (OR=1.56, 95% CI=1.01-2.21, p=.01), thus we stratified the regression model by sex to identify specific risk factors for suicide plan and/or attempt for males and females. Among males, having no confidant (OR=2.13, 95% CI=1.19-3.80, p=.01), presence of recent stressors (OR=1.95, 95% CI=1.16-3.29, p=.01), and participation in social activities (OR=1.67, 95% CI=1.02-2.71, p=.04) were important predictors, while among females, younger age (OR=0.96, 95% CI=0.94-0.97, p<.001) increased odds of suicide plan and/or attempt. Conclusion: EMR-derived findings highlight different psychosocial and clinical determinants for males and females associated with suicide plan or attempt prior to psychiatric admission. Identifying precipitating factors that elevate imminent suicide risk may inform suicide prevention efforts for psychiatric inpatients.